Oral presentation Deciphering the evolution of the prokaryotes adhered to greenhouse macroplastics when its useful life is over - Vasquez Christodoulou, Marlen (My University, 2026)
Martínez-Campos S, Pissaridou P, Drakou K, González-Pleiter M, Fernández-Piñas F, Leganes F, Rosal R, Anayiotos A, Vasquez MI, Deciphering the evolution of the prokaryotes adhered to greenhouse macroplastics when its useful life is over, oral presentation, Ocean4Biotech kick-off conference, Piran, 5-6 February 2020.